THE EFFECT OF THE TEAM PAIR SOLO (TPSO) LEARNING STRATEGY ON THE IMPROVEMENT OF MAHARAH QIRA’AH AMONG GRADE VIII STUDENTS AT MTS SURYA BUANA MALANG - Putri, My Love Faizah; Machmudah, Umi; Munjiah, Ma'rifatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Team Pair Solo (TPSO) strategy on students’ reading skills (maharah qira’ah) at MTs Surya Buana Malang. This research used a quantitative approach with a one-group pretest-posttest design. Data were collected through tests, and questionnaires. While data analysis employed the Wilcoxon Signed Rank Test and N-Gain. The results show that the TPSO strategy has a significant effect on students’ reading skills. This strategy improves students’ text comprehension and engagement through structured learning stages, namely team, pair, and solo. Therefore, TPSO can be considered an effective alternative in improving students’ reading skills.